Peripherally inserted central catheters inserted with current best practices have low deep vein thrombosis and central line–associated bloodstream infection risk compared with centrally inserted central catheters: A contemporary meta-analysis. Issue 1 (January 2021) - Schears, Gregory J; Ferko, Nicole; Syed, Imran; Arpino, John-Michael; Alsbrooks, Kimberly
Background: Peripherally inserted central catheters and centrally inserted central catheters have numerous benefits but can be associated with risks. This meta-analysis compared central catheters for relevant clinical outcomes using recent studies more likely to coincide with practice guidelines. Methods: Several databases, Ovid MEDLINE, Embase, and EBM Reviews were searched for articles (2006–2018) that compared central catheters. Analyses were limited to peer-reviewed studies comparing peripherally inserted central catheters to centrally inserted central catheters for deep vein thrombosis and/or central line–associated bloodstream infections. Subgroup, sensitivity analyses, and patient-reported measures were included. Risk ratios, incidence rate ratios, and weighted event risks were reported. Study quality assessment was conducted using Newcastle–Ottawa and Cochrane Risk of Bias scales. Results: Of 4609 screened abstracts, 31 studies were included in these meta-analyses. Across studies, peripherally inserted central catheters were protective for central line–associated bloodstream infection (incidence rate ratio = 0.52, 95% confidence interval: 0.30–0.92), with consistent results across subgroups. Peripherally inserted central catheters were associated with an increased risk of deep vein thrombosis (risk ratio = 2.08, 95% confidence interval: 1.47–2.94); however, smaller diameter and single-lumen peripherally inserted central catheters were no longer associated with increased risk. The absolute risk of deep vein thrombosis was calculated to 2.3% and 3.9% for smaller diameter peripherally inserted central catheters and centrally inserted central catheters, respectively. On average, peripherally inserted central catheter patients had 11.6 more catheter days than centrally inserted central catheter patients ( p  = 0.064). Patient outcomes favored peripherally inserted central catheters. Conclusion: When adhering to best practices, this study demonstrated that concerns related to peripherally inserted central catheters and deep vein thrombosis risk are minimized. Dramatic changes to clinical practice over the last 10 years have helped to address past issues with central catheters and complication risk. Given the lower rate of complications when following current guidelines, clinicians should prioritize central line choice based on patient therapeutic needs, rather than fear of complications. Future research should continue to consider contemporary literature over antiquated data, such that it recognizes the implications of best practices in modern central catheterization.